THE EFFECT OF 3D PRINTING ON A TEXTILE FABRIC - Mežinska, Silvija; Kangro, Ilmārs; Zaicevs, Edgars; Salmane, Gunta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
3D printing capabilities are also used in the fashion and textile industries. 3D printed textiles are a new opportunity to create an individual design. Traditional textile structures can be interpreted using 3D printing technologies and materials. One of the most important factors associated with the use of 3D printing technology is to reduce the impact of processing on the physical properties of textile fabrics. Availability of 3D printers at Rezekne Academy of Technologies (RTA) provides experimental work with fabrics of different thickness and fibres as well as different filaments. This study is based on the analysis of synthetic fibre cloth processing and the effect of 3D printing parameters on textile materials. By applying successive layers of materials, the interaction between 3D printing and textiles is studied. In terms of adhesion and stability, the best adhesion parameters for a particular type of fabric are determined by analysing the type of the fabric. The variance analysis method is used to process the research results.